Beam position monitoring in pulsed high-current electron linear accelerators - Boriskin, V.N.; Gurin, V.A.; Dovbnya, A.N.; Reprintsev, L.V.; Savchenko, A.N.; Tatanov, V.I.; Shendrik, V.A. (Вопросы атомной науки и техники, 2000)
The paper presents design and test results for the channel measuring the position (relative to the accelerator axis) of the center of the electron beam with a pulse length of 4 ms, a pulse current up to 1000 mA, a pulse frequency of 150(300) Hz and energy up to 30 MeV. The measurement error was 0.5 mm for a 42 mm aperture. A magneto-inductive- type four-winding monitor was used. The signals from the monitor could be computer-processed in two ways: either by the signal peak or by the integral value of the signal. The procedure of averaging the results was provided. Two measuring channels ensuring safe beam guiding were created in the two-section electron linac “EPOS”. A three-year operation with the beam has demonstrated their reliability and convenience in service.